2021
DOI: 10.2196/25322
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality or Augmented Reality as a Tool for Studying Bystander Behaviors in Interpersonal Violence: Scoping Review

Abstract: Background To provide participants with a more real and immersive intervening experience, virtual reality (VR) and/or augmented reality (AR) technologies have been integrated into some bystander intervention training programs and studies measuring bystander behaviors. Objective We focused on whether VR or AR can be used as a tool to enhance training bystanders. We reviewed the evidence from empirical studies that used VR and/or AR as a tool for examinin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
(133 reference statements)
1
12
0
Order By: Relevance
“…In a recent meta-analysis of bystander studies that have used VR for experimental purposes or as a training tool only 11 studies (out of a possible 12,972) were found that satisfied this criteria 42 . Nine of these were experimental studies to examine factors that influence bystander behaviour, and 2 were trials of intervention programs which concentrated on presenting existing programs to encourage bystander intervention comparing the effect of using VR with video.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis of bystander studies that have used VR for experimental purposes or as a training tool only 11 studies (out of a possible 12,972) were found that satisfied this criteria 42 . Nine of these were experimental studies to examine factors that influence bystander behaviour, and 2 were trials of intervention programs which concentrated on presenting existing programs to encourage bystander intervention comparing the effect of using VR with video.…”
Section: Discussionmentioning
confidence: 99%
“…Newer research methods such as virtual reality (VR) may help provide further control in exploring these factors. Although research with VR methods on SA bystander intervention is limited, there have been promising results from the broader interpersonal violence literature (Xue et al, 2021). Using VR methods, a study could systematically generate and vary aspects of individuals in an SA situation like the visual cues for describing someone as intoxicated, the various ways that gender/sex identity are assumed by strangers, elements of race/ethnicity, and other key factors.…”
Section: Discussionmentioning
confidence: 99%
“…Opsahl et al (2021) discussed their transition from a F2F setting to an online event (via Zoom and Mentimeter 6 ) to educate employees about cyber-civility, which ultimately had equivalent outcomes to similar in-person events. Research has begun to examine novel interventions to prevent VNWB, including cyber-incivility (C. M. Clark & Dunham, 2020;Rose et al, 2020), cyber-media ethics (Permanasari et al, 2021), cyber-abuse (Seinfeld et al, 2021), bystander intervention in cyber-aggression (Rovira & Slater, 2022;Xue et al, 2021), and conflict de-escalation training for human resource employees (N. Moore et al, 2022). These include the use of online games and virtual/augmented reality simulations.…”
Section: Decreasing Ambiguitymentioning
confidence: 99%